2018
DOI: 10.1038/s41375-018-0173-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic algorithm for lower-risk myelodysplastic syndromes

Abstract: Rapid advances over the past decade have uncovered the heterogeneous genomic and immunologic landscape of myelodysplastic syndromes (MDS). This has led to notable improvements in the accuracy and timing of diagnosis and prognostication of MDS, as well as the identification of possible novel targets for therapeutic intervention. For the practicing clinician, however, this increase in genomic, epigenomic, and immunologic knowledge needs consideration in a "real-world" context to aid diagnostic specificity. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 124 publications
0
11
0
Order By: Relevance
“…Although BM aspiration and biopsy examinations are essential to definite diagnosis, quantitative estimation of peripheral blood polymorphs including dysplastic features of granulocytes has been reported as a simple and valuable diagnostic tool in MDS 22 . Dysmorphic WBCs such as hypogranular neutrophils or pseudo-Pelger-Huet cells found in the PB are suggestive to differentiate hMDS from AA 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although BM aspiration and biopsy examinations are essential to definite diagnosis, quantitative estimation of peripheral blood polymorphs including dysplastic features of granulocytes has been reported as a simple and valuable diagnostic tool in MDS 22 . Dysmorphic WBCs such as hypogranular neutrophils or pseudo-Pelger-Huet cells found in the PB are suggestive to differentiate hMDS from AA 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the availability of screening methods for somatic mutations will increasingly produce situations where the distinction between MDS and pre-MDS conditions like ICUS or CCUS is difficult. The use of mutational analysis is certainly recommended by guidelines [ 9 ], especially in low-risk MDS, but it is unclear to what extent the guidelines are followed in daily clinical practice. Data published by our group demonstrate that only a decade ago, alarmingly few elderly MDS patients were diagnosed according to the guidelines in Germany, mainly because cytogenetic analysis was omitted [ 10 ].…”
Section: Guidelines: the Key To Quality Care In Mdsmentioning
confidence: 99%
“…Myelodysplastic Syndrome (MDS) is a cluster of tumorous diseases originating from hematopoietic stem cells. It characterizes aberrant bone marrow hematopoiesis, abnormal blood cell development, manifested as refractory blood cell reduction, hematopoietic failure, and high risk of transforming to acute myeloid leukemia, once referred to as pre-leukemia [1][2]. Previous epidemiological studies have shown that the incidence of MDS in the United States, Europe, and Asia ranges from less than 2 to more than 68 per 100,000 people [3][4][5].…”
Section: Introductionmentioning
confidence: 99%